2005
DOI: 10.1038/sj.gt.3302445
|View full text |Cite
|
Sign up to set email alerts
|

Intracarotid delivery of oncolytic HSV vector G47Δ to metastatic breast cancer in the brain

Abstract: Delivery of viral vectors to tumors in the brain is a challenge, especially via systemic administration, which is key to targeting the invasive margins of malignant glioma and the multiple foci of metastatic disease. Like for other cancer therapeutics, the blood-brain barrier or even the bloodtumor barrier significantly limits delivery and efficacy. Bloodbrain barrier disruption (BBBD) is one strategy for transiting the cerebrovasculature. G47D is a third-generation oncolytic replication-competent herpes simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 45 publications
2
52
1
Order By: Relevance
“…Furthermore, within lung carcinoma and melanoma xenografts, spread of replication-competent adenovirus is restricted, similar to what was observed here (26,45). Incomplete transduction of tumors and tumor xenografts has been observed for a variety of replication-competent viruses, including attenuated measles virus (46,47), herpes simplex virus (48,49), and vesicular stomatitis virus (50), which suggests that physical barriers exist, which limit virus dissemination despite the ability to spread from cell to cell.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, within lung carcinoma and melanoma xenografts, spread of replication-competent adenovirus is restricted, similar to what was observed here (26,45). Incomplete transduction of tumors and tumor xenografts has been observed for a variety of replication-competent viruses, including attenuated measles virus (46,47), herpes simplex virus (48,49), and vesicular stomatitis virus (50), which suggests that physical barriers exist, which limit virus dissemination despite the ability to spread from cell to cell.…”
Section: Discussionsupporting
confidence: 50%
“…A variety of single agents have been utilized including nitrosoureas, platinum analogs, 5-FU, etoposide, or in combination with systemic chemotherapy 3 . IA administration techniques have also been used to deliver adenoviral 4 or HSV 5 vectors to human brain tumors in mice and rats with some evidence of inhibition of tumor growth. More recently, molecularly targeted therapies such as bevacizumab, a monoclonal antibody against VEGF, and cetuximab, an antibody against EGFR, has safely been delivered by IA infusion 6,7 .…”
Section: Resultsmentioning
confidence: 99%
“…Because of deletion of the g34.5 and ICP6 genes, HSV-G47D replicates preferentially in cancer cells while sparing neurons and other normal cells, and therefore would be safer for in vivo use. 9,10 The histological specimen of the infected tissues presented in Figure 1b demonstrated that both HSV-1(Gb) and the attenuated HSV-G47D infected equally well the human colon carcinoma tissue while sparing the healthy colon. The efficiency of infection by HSV-1(Gb) and HSV-G47D, and their tropism to the colon carcinoma tissue suggest that they may be suitable vectors for colon carcinoma applications.…”
Section: Hsv Vectors Preferentially Infect Human Colon Cancermentioning
confidence: 99%